Methodology for creating business knowledge - Arbnor, Ingeman; Bjerke, Bjo?rn (SAGE, 2009)
This book presents and compares three different methodologies for gaining business knowledge: analytic, systems and actors. The consequences of using each approach in various practical and theoretical situations are examined.
Keywords: Managerial economics : Methodology; Business : Research : Methodology; Organizational learning : Cost effectiveness; Managerial economics : Methodology; Business : Research : Methodology; Organizational learning : Cost effectiveness